Preliminary Findings On Behavioral Patterns Of The Barking Deer, Muntiacusmuntjak (Zimmermann 1780) In Captivity At Dhaka Zoo In Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2015)
This research was conducted to document behavioral patterns of the barking deer, Muntiacus muntjak (Zimmermann 1780) in captivity. All-occurrence and ad libitum sampling methods were used opportunistically to observe 15 barking deer at Dhaka Zoo in Bangladesh from April to November, 2011.A total of 54 behavioral patterns of the barking deer was recorded and described under 13 major heads. Of which, 41 behavioral patterns were similar for males and females and 13 were sex different. The highest observation was recorded for self-directed behaviors (21.55%) followed by consuming behaviors (20.84%), investigative behaviors (17.65%), scent markings and depositions (14.53%), relaxed states (13.98%), agonistic interactions (2.63%), foraging behaviors (2.31%), sexual behaviors (1.83%), submissive behaviors (1.66%), elimination (1.25%), movements (1.23%), vocalization (0.3%) and affinitive interactions (0.23%). The behavioral patterns were almost similar for male and female with several patterns showing variations. Females consumed food and took rest more frequently than males, who spent more time in foraging and movement. Males also showed higher frequency of sexual behaviors and less submissive behaviors. Environmental sniffing (n=792) was the most frequently encountered behavior and preaching (n=l) was the least. The present findings reveal that majority of the behaviors resemble that of other cervids, but nibbling and barking are unique to this species.Asiat. Soc. Bangladesh, Sci. 41(2): 233-243, December 2015